2020
DOI: 10.1093/advances/nmaa077
|View full text |Cite
|
Sign up to set email alerts
|

Tea Consumption and Risk of Cancer: An Umbrella Review and Meta-Analysis of Observational Studies

Abstract: Tea is one of the most widely consumed beverages, but its association with cancer risk remains controversial and unclear. We performed an umbrella review to clarify and determine the associations between tea consumption and various types of cancer by summarizing and recalculating the existing meta-analyses. Meta-analyses of observational studies reporting associations between tea consumption and cancer risk were searched on PubMed and Embase. Associations found to be statistically significant were further clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(52 citation statements)
references
References 41 publications
0
51
0
1
Order By: Relevance
“…Fifty-seven umbrella reviews including 3744 associations assessed by meta-analyses of observational studies were included [ 5 , 6 , 27 81 ] (Fig. 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fifty-seven umbrella reviews including 3744 associations assessed by meta-analyses of observational studies were included [ 5 , 6 , 27 81 ] (Fig. 2 and Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Meta-analyses of the proportions of convincing and highly suggestive associations across the 57 topics resulted in 1.3% (95% CI [1.0–2.2%]) summary proportion for convincing and 4.6% (95% CI [2.9–6.6%]) summary proportion for highly suggestive associations, and both had very high between-topic heterogeneity (I 2 = 73.9% and I 2 = 85.7%, respectively) (Table 3 and Additional file 2 : Figures 1 to 5). Convincing associations varied from 0 to 16.7% across topics and 29/57 umbrella reviews had no associations with convincing evidence [ 6 , 29 , 36 , 38 , 40 , 41 , 45 , 47 , 50 , 52 , 53 , 56 , 58 , 62 , 63 , 65 , 66 , 68 72 , 74 76 , 78 – 81 ] (Table 2 ). Moreover, the number of non-statistically significant associations (those with P≥0.05) varied substantially between topics from 0% for the associations of depression with mortality outcomes, antipsychotics with life-threatening events, and health factors with loneliness [ 40 , 55 , 68 ] to 80.7% for risk factors of prostate cancer [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Drinking tea is a very common and popular habit in China and is also a traditional way of leisure and entertainment. The relationship between tea drinking and cancer is still unclear while green tea is generally considered to be cancer resistant because it contains catechin or polyphenols ( 58 , 59 ). According to our study, preventive measures should be carried out for risk factors such as reducing alcohol drinking, reducing hot tea drinking, and keep proper weight.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from case-control studies suggests that GT consumption may promote reduced incidence of breast cancer [ 8 , 9 ]. A recent umbrella review and meta-analysis of observational studies regarding tea consumption and risk of cancer showed that high consumption compared with low GT consumption significantly lowered the risk of breast cancer [ 10 ]. Further investigation is needed to provide evidence of the GT role in the overall risk of cancer [ 11 ].…”
Section: Introductionmentioning
confidence: 99%